Innate Viral Receptor Signaling Determines Type 1 Diabetes Onset - Morse, Zachary J.; Horwitz, Marc S. (Frontiers in Endocrinology, 2017)
Heritable susceptibility of the autoimmune disorder, type I diabetes (T1D), only partially equates for the incidence of the disease. Significant evidence attributes several environmental stressors such as vitamin D deficiency, gut microbiome, dietary antigens, and most notably virus infections in triggering the onset of T1D in these genetically susceptible individuals. Extensive epidemiological and clinical studies have provided credibility to this causal relationship. Infection by the enterovirus, coxsackievirus B, has been closely associated with onset of T1D and is considered a significant etiological agent for disease induction. Recognition of viral antigens via innate pathogen recognition receptors induce inflammatory events which contribute to autoreactivity of pancreatic self-antigens and ultimately the destruction of insulin-secreting beta cells. The activation of these specific innate pathways and expression of inflammatory molecules, including type I and III interferon, prime the immune system to elicit either a protective regulatory response or a diabetogenic effector response. Therefore, sensing of viral antigens by RIG-I-like receptors and Toll-like receptors may be detrimental to inducing autoreactivity initiated by viral stress and resulting in T1D.